2002
DOI: 10.1097/00001756-200210280-00003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new thyroid hormone-regulated genes in rat brain neuronal cultures

Abstract: As a first approach to study the molecular mechanisms that underlie the effects of thyroid hormones on the developing brain, we used a cDNA microarray technology to identify early thyroid hormone-regulated genes in brain neuronal cultures treated with tri-iodothyronine (T3) for 3 h. We identified three genes that were up-regulated by T3, basic transcription element-binding protein, nuclear pore glycoprotein and bone morphogenetic protein-4 and one that was down-regulated, the neuronal apoptosis-inducing gene. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Therefore, an indirect regulation of nNOS expression in the cerebral cortex might not to be excluded during hyperthyroidism. The consensus sequence of TRE was not described in the nNOS promoter [3], and studies using microarray technique did not confirm the direct regulation of nNOS by TH either [22][23][24]. The latter finding implicate that the effect of TH on nNOS production, and hence activity, may occur via indirect, nongenomic pathways.…”
Section: Possible Regulatory Mechanisms Of Nnos By Thmentioning
confidence: 93%
“…Therefore, an indirect regulation of nNOS expression in the cerebral cortex might not to be excluded during hyperthyroidism. The consensus sequence of TRE was not described in the nNOS promoter [3], and studies using microarray technique did not confirm the direct regulation of nNOS by TH either [22][23][24]. The latter finding implicate that the effect of TH on nNOS production, and hence activity, may occur via indirect, nongenomic pathways.…”
Section: Possible Regulatory Mechanisms Of Nnos By Thmentioning
confidence: 93%
“…Klf9 is a T 3 target gene in several neuronal cell types (16,17). It encodes a transcription factor identified as an inhibitor of axonal regeneration in murine retinal ganglion cells (5).…”
Section: Krüppel-like Factor 9 Mediates the Inhibitory Effect Of T 3 mentioning
confidence: 99%
“…We therefore investigated the involvement of high T 3 levels in the onset of the loss of regenerative capacity of postnatal PCs. Because Krüppel-like factor 9 (Klf9) is a transcriptional target of T 3 in some neuronal cell types (16,17) and is involved in the developmental loss of regenerative ability of retinal ganglion cells (5), we also examined whether T 3 acts on PCs by regulating Klf9 expression.…”
mentioning
confidence: 99%
“…The first three genes are up-regulated and the last one down-regulated by T3 (201). Moreover, by comparing the gene expression profiles of control newborn mice at the 4th postnatal day (P4) with age-matched experimentally hypothyroid mice and hypothyroid mice treated with tiroxine, Takahashi et al (202) identified six novel TH-responsive genes expressed in the developing cerebellum: orc11, galr3, sort1, nlgn3, cdk5r2 and zfp367.…”
Section: Ontogenesis Of Th Receptors In the Brainmentioning
confidence: 99%